The effect of letrozole (aromatase inhibitorifemara) and clomiphene citrate clomid/serophene) for induction of ovulation in polycystic ovarian syndrome (PCOS) - Nik Hazlina, Nik Hussain (Pusat Pengajian Sains Perubatan, 2012)
Women who was diagnosed to have Polycystic Ovarian Syndrome (according to the revised Rotterdam ESHREIASRM criteria, 2003) (2004) attending Infertility Clinic at Hospital Sultanah Bahiyah, Alar Star, Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan and Hospital Tengku Ampuan Afzan, Kuantan, Pahang were recruited in this study. They were later randomized into two groups i.e. Letrtozole Group (Letrozole, n=75), Clomiphene Citrate Group (CC n=75). During initial visit, the Body Mass Index and Waist Circuference were measured. Baseline investigations were taken which include Follicular Stimulating Honmone, Luteinising Honmone, Liver Function Test, Renal Function Test and serum prolactin. In Letrozole Group, Letrozole 5.0 mg daily was given from the fifth until the ninth day of menstruation. Clomiphene citrate 100mg daily was given for those patients in CC Group from the fifth until the ninth day of menstruation as well. Serial tranvaginal scan were done to see the dominant follicles, endometrial thickness and number of follicles. Tranvaginal scan were repeated to look for evidence of ovulation. Total of 150 subjects enrolled in this study, completed the ovulation induction cycle and included in data analysis. There were no statistical differences noted in term of sociodemographic, antropometrics and duration of infertility in between these two studied groups suggestive that the subjects were homogenously distributed. The difference between letrozole and CC in tenm of ovulation rate, 59 (78.7%) vs 40 (53.3%); p <0.001 which was statistically significant, and pregnancy rate, 19 (25.3%) versus 12 (16.0%); p 0.22 which was statistically not significant. Letrozole also produce better dominant follicle which is monofollicle compare to CC, 33 (46.5%) versus 20 (26.7%) patients respectively. Endometrial response also yielded similar result. No incidence of adverse pregnancy outcome like Ovarian Hyperstimulation Syndrome (OHSS) observing in this study. Multiple logistic regression (MLR) shows letrozole group had three times more likely having ovulation outcome compare to CC group after controlling other variables of age, duration of infertility, type of infertility, baseline honmonal profile and BMI. Only BMI made significant contribution to predict successful ovulation. If BMI of a patient increases by 1 unit kg/m2 , there is a nine percent of chance of her to have successful ovulation. Letrozole provide a more efficient stimulation to CC in tenm of ovulation induction, thicken the endometrial lining and achieving a successful pregnancy among PCOS women undergoing ovulation induction.